2022
DOI: 10.7150/thno.69938
|View full text |Cite
|
Sign up to set email alerts
|

3D culturing of human pluripotent stem cells-derived endothelial cells for vascular regeneration

Abstract: Rationale: Human induced pluripotent stem cell-derived endothelial cells can be candidates for engineering therapeutic vascular grafts. Methods: Here, we studied the role of three-dimensional culture on their characteristics and function both in vitro and in vivo . Results: We found that differentiated hPSC-EC can re-populate decellularized biomatrices; they remain viable, undergo maturation and arterial/ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…5) Although artificial blood vessels have been constructed from vascular cells by forming two-layer microtubes 6) using light-curing resin, the fabrication of vascular features, such as multiple bifurcations, has posed a challenge. Moreover, in the three-dimensional culturing method, where endothelial cells are contained in hydrogel implants, 7) the products were transplanted into rats and dogs to confirm the formation of capillary structures. However, the strength of a monolayer structure of matured vascular endothelial cells is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…5) Although artificial blood vessels have been constructed from vascular cells by forming two-layer microtubes 6) using light-curing resin, the fabrication of vascular features, such as multiple bifurcations, has posed a challenge. Moreover, in the three-dimensional culturing method, where endothelial cells are contained in hydrogel implants, 7) the products were transplanted into rats and dogs to confirm the formation of capillary structures. However, the strength of a monolayer structure of matured vascular endothelial cells is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to maintain the stemness and maximize the efficacy of cultured stem cells before harvesting these cells. Three-dimensional (3D) culture technology can mimic a more actual and beneficial physiological environment through cell to cell and cell to matrix interaction [ [19] , [20] , [21] ]. In addition, previous studies have demonstrated that mesenchymal stem cells (MSCs) cultured in 3D condition possess an enhanced stemness and improved therapeutic effects [ 14 , 22 ].…”
Section: Introductionmentioning
confidence: 99%